Tsunamis: does anybody have to die? Report of the Working Group on Tsunamis to the Prime Minister's Science, Engineering and Innovation Council - Pokrant, Bob (Prime Minister's Science, Engineering and Innovation Council, 2005)
This paper identifies the impact on Australia and the Asian region of the recent tsunami and the likelihood of similar disasters in the future, compares the extent and reliability of tsunami alert and effective warning systems in the Indian and Pacific Oceans, outlines Australia's research capability in the prediction, modelling, identification and risk management of tsunamis, discusses emergency management, particularly coordination and cooperation between relevant agencies that will provide effective public alerts about tsunamis and similar disasters and manage the national response, and examines ways to build Australia's scientific profile and role globally to collaborate and assist the Australasian region in natural disaster management. (From Libraries Australia, Record ID 40012763)